Tax Avoidance: How Board of Directors Diversity Strategies are Applied in Facing Tax Audits? - Nita Andriyani Budiman; Bandi (HM Journals, 2023)
This study aims to provide empirical evidence about the determinants of tax avoidance with tax audit as a moderating variable in energy companies in Indonesia. The determinants of tax avoidance referred to are the diversity of the board of directors (gender, education, and experience in office). The population of this research are all energy companies listed on the Indonesia Stock Exchange in 2016-2021. The sampling technique is purposive sampling which resulted in 102 observations. The results of testing show that the tax audit strengthens the effect of the gender diversity of the board of directors on tax avoidance, while the tax audit weakens the effect of educational diversity and experience serving the board of directors on tax avoidance.